Apuntes sobre la «guerrillerización» de la cultura: Las venas abiertas de América Latina, el Premio Casa de las Américas y los debates sobre los intelectuales y la revolución - Aguirre, Carlos (2022)
Open Veins of Latin America, by Uruguayan writer Eduardo Galeano, one of the most emblematic books of social thought in Latin America during the second half of the 20th century, was first published in 1971. Before it went into print, Galeano submitted his manuscript that same year to the Casa de las Américas Prize contest in the essay category, but came short of winning. Using as a point of departure the anecdotal fact that a book that would eventually become a classic did not receive the Casa de las Américas Prize, this article reconstructs Cuba’s complex political and cultural environment between 1968 and 1971; the tensions around literary contests promoted by the most important institutions of the Revolution; and, more generally, the debate around the role of Latin American intellectuals in the process of political and social transformation in the 1960s.